Does Village Fund Reduce Poverty and Disparity in East Java Province? (Evidence from Indonesia) - Suseno, Vimbyarno Purbo; Syafitri, Wildan; Bintoro, Nugroho Suryo (Journal of International Conference Proceedings, 2023)
From economic perspective, poverty arises as result of lack of access to capital and resources differences as explained in the vicious circle of poverty theory. In addition, differences in each region and various factors then create developed regions and underdeveloped regions. Developed regions are progressing and becoming a magnet for the capital, investment and residents of underdeveloped areas. Meanwhile, underdeveloped regions remain. Statistical data shows that the poverty rate is greater in rural areas than in urban areas. For this reason, the government's policy to overcome poverty and disparity is to carry out development from marginal areas, namely rural areas. With the enactment of Law Number 6 of 2014, the village becomes an autonomous region to be able to regulate dan manage its community including aspects of planning, development, finance, and democracy independently. Since 2015, the government has allocated Village Funds to villages originating from the State Budget in the amount of 10% of and excluding Regional Transfers allocated in the State Budget. The results of the study show that Village Funds significantly reduces poverty, but it has no impact on disparity.